Peran Pendidikan Multikultural pada Perspektif Islam dalam Membentuk Karakter Toleransi Peserta Didik di Sekolah - Yuliana Yuliana; Sapuadi Sapuadi (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2026)
This research is very important to understand more deeply about the Islamic-based multicultural education approach in forming a character of tolerance, as well as how to apply this approach in the educational environment. This research uses a qualitative approach with the type of literature study (library research). This approach is used to examine in depth the concept of multicultural education in an Islamic perspective and introduce it in forming the character of tolerance of students through the analysis of various relevant library sources. Multicultural education basically aims to create a harmonious society through an educational process that respects differences and eliminates discrimination. In this case, multicultural education is a strategic solution because it does not only focus on cognitive aspects, but also on the formation of social attitudes, such as tolerance, empathy, and inclusive attitudes. In its implementation, multicultural education aims to enable students to appreciate differences, foster a tolerant attitude, and strengthen national identity within the framework of diversity. Therefore, the application of multicultural education needs to continue to be developed optimally in the education system in order to create a harmonious, inclusive, and character-based learning enviroment.